Soluble Silicon Source via Foliar Application Improve Plant Physiology and Fruit Quality of Solanum lycopersicum L. - Flores, Rilner Alves; de Lima, Frederico Simões Raimundo; Xavier, Maxuel Fellipe Nunes; Bueno, Amanda Magalhães; de Andrade, Aline Franciel; de Souza Júnior, Jonas Pereira [UNESP]; Campos, Cid Naudi Silva; Cunha Júnior, Luís Carlos; Oliveira Abdala, Klaus de; de Mello Prado, Renato [UNESP] (Springer Nature, 2024)
The aim of this study was to evaluate the foliar application of silicon on the silicon (Si) leaf content, photosynthetic parameters, and fruit production and quality of tomato. We evaluated five silicon concentrations via foliar application: 0 (control), 1, 2, 3 and 4 g L−1 of Si in tomatoes, using stabilized potassium copper silicate (SiKCuE) as a Si source. The foliar applications were carried out at the beginning of flowering, at intermediate flowering, and at full flowering. One week after the third application of Si, the relative chlorophyll index (RCI), physiological quality and Si content were measured on the diagnostic leaf. When the fruits had reached full maturity, they were harvested, the productivity was estimated, and the firmness and soluble solids content were evaluated. Foliar application of Si, proved to be efficient in increasing the leaf content of the beneficial element in tomato plants. The Si concentration of 2.34 g L−1 resulted in a leaf silicon content of 17.3 g kg−1, indicating the ideal Si content in tomato leaves, related to higher productivity (124.4 t ha−1). As a result foliar application of Si as SiKCuE is efficient in supplying Si via leaf to tomato plants, favoring photosynthetic parameters and fruit production and quality by increasing, accumulation of soluble solids firmness. The application of Si proved to be economically viable for all evaluated concentrations, allowing maximum profit to be obtained, US$ 6,679.00 ha−1 at a concentration of 3 g L−1 de Si, which produced 12% more than the control treatment, without the addition of silicon.
Keywords: Abiotic stress; Foliar fertilization; Reactive oxygen species; Tomato